De l’histoire des émotions à la généalogie de la subjectivité - Ondřej Švec (Acta Universitatis Carolinae: Philologica, 2018)
Recent historical works dealing with the changing role of emotions in social and private life over centuries present a challenge to any philosophical or scientific theory aiming to grasp the essence of emotions. The paper identifies several methodological difficulties that all inquiries into past forms of emotional life are inevitably faced with. Then, it develops three philosophical lessons from the vast overview gathered by par A. Corbin, J.-J. Courtine and G. Vigarello in three recent volumes of their History of emotions. The first conceives of the radical historicity of emotions as an argument against reductionist accounts of emotions in contemporary affective neuroscience, according to which emotions are best explained as autonomous physiological responses to a changing environment. The second lesson makes explicit the methodological postulate of many historical investigations that assimilates the emotional experiences with their narrative traces in literature, autobiography and correspondence. It also provides several reasons justifying the indivisibility of emotions from their expression. The final lesson develops a novel genealogy of subjectivity stemming from the study of our past “emotional regimes”. Contemporary psychology and neurobiology – the author argues – shapes a new conception of ourselves, making visible and manageable our emotional life in a way that is undoubtedly more informal and democratic, but nevertheless subjected to new forms of control through different incentives to account for what we feel.